C–C couplings in water by micellar catalysis at low loadings from a recyclable polymer-supported Pd(ii)–NHC nanocatalyst. Issue 4 (6th December 2018) - Lambert, Romain; Wirotius, Anne-Laure; Vignolle, Joan; Taton, Daniel
Abstract : A robust and recyclable polymer-supported Pd(ii )–NHC2 nanocatalyst enables highly efficient micellar catalysis of the Suzuki–Miyaura reaction at low loadings with a broad substrate scope. Abstract : A specifically devised amphiphilic star-like polymer-supported Pd(ii )–NHC2 unit (NHC = N-heterocyclic carbene) enables highly efficient micellar catalysis in pure water. An amphiphilic block copolymer carrying benzimidazolium moieties randomly distributed along the hydrophobic block is precisely synthesized by reversible addition fragmentation chain transfer (RAFT) polymerization. Addition of Pd(OAc)2 followed by nanoprecipitation in water drives the metal–ligand coordination core-crosslinking reaction and the segregation of Pd–NHC2 units in the hydrophobic core to form robust polymeric micelles. This approach confers multiple advantages to both the Suzuki–Miyaura and Heck cross-coupling reactions, including robustness, almost no metal leaching, low catalyst loadings (0.1 mol% rel. to the substrate), easy recycling, very broad substrate scope and exceptionally high catalytic activity in water.